Pengaruh Kompetensi Pedagogik dan Profesionalisme Guru Terhadap Prestasi Belajar Siswa Pada SMA se-Kecamatan Amalatu-Elpaputih - Viona Wairatta; Th. Laurens; A. Sahalessy; Sumarni Rumfot (LP. Ma'arif Janggan Magetan, 2024)
The impact of teachers's pedagogical competence and professionalism on student learning achievement in high school in Amalatu-Elpaputih District. A teacher's pedagogical and professional competence is needed to improve the quality of learning and student achievement. This research was conducted with the aim of looking at the influence of teachers' pedagogical and professional competence on the learning achievement of high school students in the amalatu-elpaputih sub-district, western Seram district. This type of research is quantitative, with the number of samples selected using a saturated sampling technique being 80 people. The technique used to obtain this is through a closed questionnaire. Regression test statistics show that (1) there is a positive and significant influence of teacher pedagogic competence on the learning achievement of State High School students in the Amalatu-Elpaputih subdistrict, SBB district. This influence can be explained through the regression model formed, namely . The magnitude of the influence of pedagogical competence on student learning achievement, namely 34.30% and 65.70%, is another factor outside this regression model; (2) there is a positive and significant influence of teacher professionalism on the learning achievement of State High School students in the Amalatu-Elpaputih sub-district, SBB district. This influence can be explained through the regression model formed, namely . The influence of teacher professionalism on student learning achievement is 27.60%, and the remaining 72.40% is other factors outside this regression model; and (3) there is a positive and significant influence of pedagogical competence and teacher professionalism on the learning achievement of State High School students in the Amalatu-Elpaputih subdistrict, SBB district. This influence can be explained through the regression model formed, namely . The magnitude of the influence of pedagogical competence and teacher professionalism on student learning achievement, namely 38.60% and 61.40%, is another factor outside this regression model.